BIMBINGAN TEKNIS PENGUATAN AKREDITASI PENDIDIK DAN TENAGA KEPENDIDIKAN PAUD AISYIYAH SE KOTA KENDARI - Nurlina Nurlina; Asrul Asrul; Halima Halima (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2024)
This service activity aims to improve the quality of education in Early Childhood Education by providing technical guidance to educators and education staff. The main focus of this activity is to provide an in-depth understanding of the accreditation process, improve practical skills in preparing accreditation documents, and design management improvements that positively impact the overall evaluation process. The implementation of community service activities is carried out through three stages, namely the preparation stage, the implementation stage, and the monitoring and evaluation stage. With this collaboration, it is hoped that educators and education personnel can face and undergo the accreditation process better, positively contribute to the quality of education, and create sustainable changes in the ECCE environment. Hopefully, this effort will assist educators and education staff and increase understanding of accreditation preparation instruments so institutions can achieve superior accreditation scores in every accreditation assessment implementation.